2015
DOI: 10.4103/1012-5574.156103
|View full text |Cite
|
Sign up to set email alerts
|

Phonological awareness deficits in Arabic-speaking children with learning disabilities

Abstract: BackgroundPhonological awareness refers to the language ability to perceive and manipulate the sounds of spoken words. It is an understanding of the structure of spoken language -that it is made up of words, and that words consist of syllables, rhymes, and sounds. The presence of a relationship between performance in phonological awareness tasks and reading ability is undisputed. Materials and methods100 normal children together with 30 learning -disabled children were evaluated with the Arabic phonological aw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…In a study that compared phonological awareness abilities between typical Arabspeaking children and Arab children with learning disabilities, Barakah et al (2015) found that children with learning disabilities scored significantly poorer than typical children in most phonological awareness skills. Indeed, several researchers (e.g., Ammar & Ridha, 2013) reported that poor readers lack phonemic awareness abilities.…”
Section: Phonological Awareness Researchmentioning
confidence: 99%
“…In a study that compared phonological awareness abilities between typical Arabspeaking children and Arab children with learning disabilities, Barakah et al (2015) found that children with learning disabilities scored significantly poorer than typical children in most phonological awareness skills. Indeed, several researchers (e.g., Ammar & Ridha, 2013) reported that poor readers lack phonemic awareness abilities.…”
Section: Phonological Awareness Researchmentioning
confidence: 99%